A STUDY OF VERBS OF MATCHING IN ENGLISH AND THEIR VIETNAMESE TRANSLATIONAL EQUIVALENTS - M.Ed Phan Thị Bé (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Understand about EMVs , its syntactic and semantic features in English .